BODY OF KNOWLEDGE PENDIDIKAN DASAR - Komar, Oong (PEDAGOGIA, 2014)
Animo three-UPI SPs Studies Program in the last two years tops the list, which amounts to 210 to 230 applicants for a course of English language education, physical education and basic education. The number of open interest pendas, whether perceptions about pendas value-oriented labor market scientifics and practical benefits? Does science have the formula pendas slices (formal object) by itself and does not duplicate the study program in the same direction? Is basic education is still conceived within the paradigm of primary education/elementary school, compulsory education, general education, and education for all? To answer these questions, the data collected with the Delphi technique of respondent students, alumni, users, structural and experts. If not, then there will be a basic education in the surface. Implications on the basic education curriculum prepared based on principles and human needs Indonesia. Such as: to understand him well; Another man with good understanding; understand the relationship with the creator; and understand nature well. Basic education or education for all or compulsory education, thesame meaning is to be good a citizenship, becoming good citizens.Keywords: basic education, primary education/elementary school, compulsory education, generaleducation, education for all.